Effect of treatments on the progression of COPD: report of a workshop held in Leuven, 11–12 March 2004. Issue 4 (24th March 2005) - Decramer, M; Gosselink, R; Bartsch, P; Löfdahl, C-G; Vincken, W; Dekhuijzen, R; Vestbo, J; Pauwels, R; Naeije, R; Troosters, T
Abstract : During the last decade several long term studies of interventions in patients with COPD have been published. This review analyses the potential of these interventions to alter the progression of the condition. The only treatment that has unequivocally been shown to reduce the rate of decline in FEV1 is smoking cessation. Active psychological intervention in combination with pharmacotherapy is required. Other treatments may have an effect on the rate of decline in FEV1 but this appears to be very small, at most. Several treatments affect the exacerbation rate and therefore might affect the progression of the disease. Further studies are warranted to examine this effect.